Knockout of NMDA-receptors from parvalbumin interneurons sensitizes to schizophrenia-related deficits induced by MK-801 - Bygrave, A; Masiulis, S; Nicholson, E; Berkemann, M; Barkus, C; Sprengel, R; Harrison, P; Kullmann, D; Bannerman, D; Kätzel, D (Nature Publishing Group, 2016)
It has been suggested that a functional deficit in NMDA-receptors (NMDARs) on parvalbumin (PV)-positive interneurons (PV-NMDARs) is central to the pathophysiology of schizophrenia. Supportive evidence come from examination of genetically modified mice where the obligatory NMDAR-subunit GluN1 (also known as NR1) has been deleted from PV interneurons by Cre-mediated knockout of the corresponding gene Grin1 (Grin1(ΔPV) mice). Notably, such PV-specific GluN1 ablation has been reported to blunt the induction of hyperlocomotion (a surrogate for psychosis) by pharmacological NMDAR blockade with the non-competitive antagonist MK-801. This suggests PV-NMDARs as the site of the psychosis-inducing action of MK-801. In contrast to this hypothesis, we show here that Grin1(ΔPV) mice are not protected against the effects of MK-801, but are in fact sensitized to many of them. Compared with control animals, Grin1(ΔPV)mice injected with MK-801 show increased stereotypy and pronounced catalepsy, which confound the locomotor readout. Furthermore, in Grin1(ΔPV)mice, MK-801 induced medial-prefrontal delta (4 Hz) oscillations, and impaired performance on tests of motor coordination, working memory and sucrose preference, even at lower doses than in wild-type controls. We also found that untreated Grin1(ΔPV)mice are largely normal across a wide range of cognitive functions, including attention, cognitive flexibility and various forms of short-term memory. Taken together these results argue against PV-specific NMDAR hypofunction as a key starting point of schizophrenia pathophysiology, but support a model where NMDAR hypofunction in multiple cell types contribute to the disease.